1
$\begingroup$

After the demonstration of the inequality of Cauchy-Schwarz make by my professor, I still don't understand some steps of the demonstration.

To prove this inequality, my professor use the induction princile.

First, verify $P(1)$. \begin{align} \big(\sum^1{a_kb_k}\big)^2 &\le \big(\sum^1{a_k^2}\big)\big(\sum^1{b_k^2}\big) \\ \big(a_1b_1\big)^2 &= a_1^2b_1^2 \end{align}

We can also verify $P(2)$. \begin{align} \big(\sum^2{a_kb_k}\big)^2 &\le \big(\sum^2{a_k^2}\big)\big(\sum^2{b_k^2}\big) \\ \big(a_1b_1+a_2b_2\big)^2 &\le \big(a_1^2+a_2^2\big)\big(b_1^2+b_2^2\big) \\ a_1^2b_1^2+2a_1b_1a_2b_2+a_2^2b_2^2 &\le a_1^2b_1^2+a_1^2b_2^2+a_2^2b_1^2+a_2^2b_2^2 \\ 2a_1b_1a_2b_2 &\le a_1^2b_2^2+a_2^2b_1^2 \\ 0 &\le a_1^2b_2^2+a_2^2b_1^2 -2a_1b_1a_2b_2 \\ 0 &\le \big(a_1b_1-a_2b_2\big)^2 \end{align}

If we suppose $P(n)$ to be true, we can verify $P(n+1)$. \begin{align} \big(\sum^{n+1}{a_kb_k}\big)^2 &\le \big(\sum^{n+1}{a_k^2}\big)\big(\sum^{n+1}{b_k^2}\big) \\ \end{align}

By the inequality of the triangle, we can write the follow statement. $$\left|\sum^{n+1}{a_kb_k}\right| \le \left|\sum^{n}{a_kb_k}\right|+\left|a_{n+1}\right|\left|b_{n+1}\right|$$ So, we can assume, $$\left|\sum^{n+1}{a_kb_k}\right| \le \sqrt{\sum{a_k^2}}\sqrt{\sum{b_k^2}}+\left|a_{n+1}\right|\left|b_{n+1}\right|$$ because we know, $$\left|\sum{a_kb_k}\right| \le \sqrt{\sum{a_k^2}}\sqrt{\sum{b_k^2}}$$ If we define $A_1=\sqrt{\sum{a_k^2}}$, $B_2=\sqrt{\sum{b_k^2}}$, $A_2=\left|a_{n+1}\right|$ and $B_2=\left|b_{n+1}\right|$ we can write this inequation like this : $$\left|\sum^{n+1}{a_kb_k}\right| \le A_1B_1+A_2B_2$$ And than, there, it's where I don't understand... $$\left|\sum^{n+1}{a_kb_k}\right| \le \sqrt{A_1^2+A_2^2}\sqrt{B_1^2+B_2^2}$$

And why we have to verify $P(2)$.

$\endgroup$
  • 1
    $\begingroup$ It's not true, as plugging almost any values into it will show. With $=$ replaced for $\leq$, this is the Cauchy-Schwarz inequality, essentially. $\endgroup$ – Thomas Andrews Jan 21 '15 at 22:13
  • $\begingroup$ Yes. My mistake. But I still don't understand why. $\endgroup$ – hlapointe Jan 21 '15 at 22:14
  • 1
    $\begingroup$ I think we need more context. $\endgroup$ – mick Jan 21 '15 at 22:14
  • $\begingroup$ what are these steps that you don't understand?? $\endgroup$ – Surb Jan 21 '15 at 22:48
  • 1
    $\begingroup$ Many nice proofs of Cauchy-Schwarz can be found on this thread: math.stackexchange.com/questions/436559/… $\endgroup$ – littleO Jan 21 '15 at 23:29
1
$\begingroup$

Actually, this expression is Cauchy-Schwarz's inequality itself. I'll give a proof and I hope you can follow. We have that $$(A_1+tB_1)^2 + (A_2+tB_2)^2 \geq 0$$ for all $t \in \Bbb R$, for being a sum of squares. This is equivalent to: $$(A_1^2+A_2^2)+2(A_1B_1+A_2B_2)t + (B_1^2+B_2^2)t^2 \geq 0.$$ This a polynomial in $t$ which is always positive, so $\Delta \leq 0$. Seeing this as $at^2+bt + c$, we have that $a = B_1^2+B_2^2, b = 2(A_1B_1+A_2B_2)$ and $c = A_1^2+A_2^2$, if this helps you seeing it. Then: $$\Delta = b^2-4ac = 4(A_1B_1+A_2B_2)^2-4(A_1^2+A_2^2)(B_1^2+B_2^2) \leq 0,$$ so that dividing by $4$ and taking roots, results $$|A_1B_1+A_2B_2| \leq \sqrt{A_1^2+A_2^2}\sqrt{B_1^2+B_2^2}.$$

$\endgroup$
2
$\begingroup$

Just notice that: $$(A_1^2+A_2^2)(B_1^2+B_2^2)-(A_1 B_1+A_2 B_2)^2 = (A_1 B_2 - A_2 B_1)^2 \geq 0.\tag{1}$$ $(1)$ is also known as Lagrange's identity.

$\endgroup$
  • $\begingroup$ How can I use this identity to prove $A_1B_1+A_2B_2\le\sqrt{A_1^2+A_2^2}\sqrt{B_1^2+B_2^2}$? $\endgroup$ – hlapointe Jan 21 '15 at 22:18
  • $\begingroup$ @hlapointe: $(1)$ proves $(A_1 B_1+A_2 B_2)^2 \leq (A_1^2+A_2^2)(B_1^2+B_2^2)$. $\endgroup$ – Jack D'Aurizio Jan 21 '15 at 22:19
  • $\begingroup$ I still like Baby rudin's method... $\endgroup$ – Troy Woo Jan 21 '15 at 23:06
0
$\begingroup$

My favorite proof: WLOG $\sum{a_k^2}=1$ and $\sum{b_k^2}=1$, then it's equivalent to showing $$\pm 2\sum{a_kb_k} \le 2\sqrt{\big(\sum{a_k^2}\big)\big(\sum{b_k^2}\big)}=\big(\sum{a_k^2}\big)+\big(\sum{b_k^2}\big),$$ which follows from $\pm 2ab\le a^2+b^2$.

$\endgroup$
0
$\begingroup$

One proof of (the real case) of the Cauchy-Schwarz inequality is via Lagrange's identity: $$\left( \sum_{i=1}^{n} a_{i}^{2} \right)\left( \sum_{i=1}^{n} b_{i}^{2} \right) = \left( \sum_{i=1}^{n} a_{i}b_{i} \right)^{2} + \sum_{i <j} (a_{i}b_{j} - a_{j}b_{i}) ^{2} .$$ There is a similar complex version too.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.